Giovani e Longevi insieme per promuovere la salute - Pili, Roberto; Carrogu, Gian Pietro; Gaviano, Luca; Petretto, Donatella Rita (UNICApress, 2023)
Recent events related to the spread of Covid-19 impose increasingly pressing reflections on the promotion of health, long and good life and the organization of interventions aimed at the prevention of diseases. It is now well-established that health promotion takes the form of individual and collective daily actions that enable each individual to live in a condition of well-being and good quality of life, even in the presence of possible pathologies; an important role in this area is played by the concept of diet in a broad sense that includes not only nutrition but that biopsychosocial interweaving of lifestyles, physical activity, nutrition and relationality. Despite this seemingly widespread awareness, we are witnessing a gap between progressive increases in life expectancy worldwide and healthy life expectancy; the progressive aging of the population is associated with an increasing prevalence of "noncommunicable diseases," which just happen to have at their base a central role of diet, in that broad sense just described. Europe, Italy and Sardinia in particular represent privileged observers because on the one hand they are characterized by a faster aging of the populationbut also by a progressive dietary transition that greatly influences the spread of noncommunicable diseases especially in some of the most exposed segments of the population.